Novel Inhibitors of SARS-CoV-2 RNA Identified through Virtual Screening - Mathez, Gregory; Brancale, Andrea; Cagno, Valeria (Journal of chemical information and modeling, 2024)
We currently lack antivirals for most human viruses. In a quest for new molecules, focusing on viral RNA, instead of viral proteins, can represent a promising strategy. In this study, new inhibitors were identified starting from a published crystal structure of the tertiary SARS-CoV-2 RNA involved in the -1 programmed ribosomal frameshift. The pseudoknot structure was refined, and a virtual screening was performed using the repository of binders to the nucleic acid library, taking into consideration RNA flexibility. Hit compounds were validated against the wild-type virus and with a dual-luciferase assay measuring the frameshift efficiency. Several active molecules were identified. Our study reveals new inhibitors of SARS-CoV-2 but also highlights the feasibility of targeting RNA starting from virtual screening, a strategy that could be broadly applied to drug development.
Keywords: simulace molekulového dockingu; Models, Molecular; RNA, Viral; Nucleic Acid Conformation; Antiviral Agents; lidé; uživatelské rozhraní počítače; Drug Evaluation, Preclinical; RNA virová; Molecular Docking Simulation; molekulární modely; User-Computer Interface; konformace nukleové kyseliny; Humans; antivirové látky; preklinické hodnocení léčiv; SARS-CoV-2